Family Quality Measurement Tool for Adolescents: Development and Validation Using the Rasch Model - Dody Hartanto; Mufied Fauziah; Salleh Amat; Diki Herdiansyah; Yenni Rizal; Nadia Aulia Nadhirah; Aisha Nadya (Universitas PGRI Yogyakarta, 2026)
This study aimed to develop and validate a family quality scale for adolescents as a contextual and practical measurement tool for guidance and counseling services. Unlike existing instruments that predominantly adopt universal family constructs, this scale was developed based on eight family functions in the Indonesian context: religious, socio-cultural, love and affection, protection, reproduction, socialization and education, economic, and environmental functions. This approach allows the instrument to reflect the characteristics of family life within a local cultural framework. The study employed a mixed-methods design. The qualitative approach involved content validation by two experts using Gregory’s method, while the quantitative approach was used to empirically test the instrument’s validity and reliability with the Rasch Model. The field trial involved 1,823 senior high school students in Yogyakarta and Pontianak, selected through random sampling. Data were collected via Google Forms distributed by school guidance and counseling teachers. The analysis results indicated that the instrument demonstrated strong validity and reliability, as evidenced by a raw variance explained of 81.5%, fulfillment of unidimensionality criteria, and an optimal response category structure. These findings confirm that the developed scale accurately and consistently measures adolescent family quality. In practice, this instrument can be used by school counselors as an initial assessment tool to plan family-based counseling interventions and to support further research in the field of guidance and counseling. Keywords: family quality, measurement scale, rasch model, reliability, validity